Polylactic acid / nanocellulose composite microneedle patch and preparation method thereof
By forming a polylactic acid drug release needle tip and a compatible bonding interlayer on the nanocellulose patch layer substrate, the existing microneedle patches have been solved, and an efficient and safe transdermal drug delivery system has been achieved.
Patent Information
- Application Number
- CN202411805758.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
AI Technical Summary
Existing microneedle patches have insufficient drug loading and drug delivery efficiency in transdermal drug delivery systems, and the mechanical strength of most polymers is not as strong as silicon and metal materials, which affects the effective penetration and absorption of drugs.
The mechanical properties and drug loading of the microneedle are improved by forming a compatible bonding interlayer between the polylactic acid drug-release needle tip and the nanocellulose patch layer containing porous chitin microspheres on the nanocellulose patch layer substrate.
It has achieved microneedle patches with high biocompatibility, low toxicity, low cost, excellent mechanical properties and green and environmentally friendly, which has improved the permeability and absorption efficiency of the drug and enhanced the effectiveness of drug delivery.
Smart Images

Figure CN119679689A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microneedle patches, and in particular to a polylactic acid / nanocellulose composite microneedle patch and a preparation method thereof. Background Art
[0002] Traditional routes of drug administration, such as oral, parenteral, and topical, have many limitations in terms of drug absorption and permeability. This affects the effectiveness of drugs in terms of patient care. Therefore, many new approaches have been studied and adopted to overcome these limitations. Among these new approaches, microneedles are one of the best choices. Microneedles are structures with micrometer-sized penetrating needles. They can be used as transdermal drug delivery systems (TDDS) to allow drugs to penetrate into different skin layers more effectively. Microneedles have great potential to improve the efficacy of many drugs by increasing the permeability of drugs in the skin. In addition, the mobile medium improves patient compliance in different aspects, such as less pain, ease of use, and no need for skilled or trained personnel to apply. In the future, the development of microneedles and their applications may occupy an important position in patient healthcare. Transdermal drug delivery systems (TDDS) have become one of the hot areas of drug delivery research due to their advantages over oral and injection administration. Therefore, TDDS has become a growing field for the systemic and local delivery of drugs, immunobiological agents, and macromolecules. In addition, the poor permeability of TDDS through the stratum corneum (SC) is also a common disadvantage of TDDS. This limitation can be overcome by using novel innovative approaches such as microneedles (MNs). Therefore, many researchers have begun to use microneedles to overcome other limitations associated with TDDS and the stratum corneum as an obstacle. A lot of research and development is currently underway on the use of microneedles themselves or in combination with TDDS. As a result, various types of porous media have been developed to more effectively deliver drugs during use while minimizing algae content. In addition, micro-nano technology based on biosensors has become an emerging trend in early diagnosis and simultaneous treatment. In 2019, Rongyan He et al. mixed polyvinyl alcohol (PVA) and chitosan to form a hydrogel to make a microneedle patch for skin interstitial-based point-of-care detection. The microneedle causes minimal damage to skin tissue and does not cause acute pain. In 2023, Ayesha Younas et al. prepared microneedles using chitosan and fucoidan for the first time, which have natural antibacterial properties, good biodegradability and biocompatibility, and are feasible and superior in achieving high-quality wound healing. However, the mechanical strength of most polymers is not as good as that of silicon and metal materials, and there may also be certain defects in drug loading and drug delivery efficiency. Polylactic acid (PLA) has become a polymer material with broad application prospects in the biological and medical industries due to its excellent mechanical properties, biocompatibility, biodegradability, low toxicity, and low cost. In 2019, Kang Tingting used thermoplastic polyurethane elastomer to modify polylactic acid to prepare microneedle products with higher toughness and better mechanical strength. Those skilled in the art are in urgent need of developing a polylactic acid / nanocellulose composite microneedle patch and its preparation method to meet existing application needs and performance requirements. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, the present invention aims to provide a polylactic acid / nanocellulose composite microneedle patch and a preparation method thereof.
[0004] A polylactic acid / nanocellulose composite microneedle patch, comprising a nanocellulose patch layer substrate and a microneedle array; the microneedle array is formed on the nanocellulose patch layer substrate; the microneedles are composite microneedles, comprising a polylactic acid drug-releasing needle tip containing porous chitosan microspheres, a nanocellulose patch layer, and a compatible bonding interlayer using a bonding agent between the polylactic acid drug-releasing needle tip containing porous chitosan microspheres and the nanocellulose patch layer.
[0005] Nanocellulose has two sources: chemical and biological fermentation. The raw materials for chemical nanocellulose include wood, cotton, wheat straw, mulberry bark, ramie, and algae fiber, while the raw materials for biological fermentation nanocellulose are bacterial cellulose.
[0006] Furthermore, the system materials are all biodegradable components, including polylactic acid, porous chitosan microspheres, nanocellulose and adhesives for compatible bonding interlayers.
[0007] Furthermore, the porous chitosan microspheres are porous microspheres with a diameter of 20 to 200 micrometers and are woven and wound by chitosan nanofibers.
[0008] Furthermore, the adhesive for the compatible bonding interlayer is any one of polypropylene glycol, polyethylene glycol, and polyethylene glycol-b-polypropylene glycol copolymer, or a mixed solution of two of the two.
[0009] Furthermore, the nanocellulose patch layer substrate has a size of 15 mm×15 mm.
[0010] Furthermore, the microneedle has a length of 600 μm, a bottom side length of 300 μm×300 μm, a needle tip spacing of 600 μm, and an array quantity of 20×20.
[0011] The preparation method of the above-mentioned polylactic acid / nanocellulose composite microneedle patch comprises the following steps: (1) Preparation of the slurry: prepare polylactic acid (PLA) into a dichloromethane solution with a final mass concentration of 8% to 10%; prepare a binder polypropylene glycol or polyethylene glycol or polyethylene glycol-b-polypropylene glycol copolymer into an ethanol binder solution with a final mass concentration of 5% to 6.25%; take nanocellulose and add it into water for homogeneous dispersion to prepare a nanocellulose slurry with a mass volume concentration of 0.5 to 0.6 g / L; (2) Add 5%-10% of dry porous chitosan microsphere powder to the polylactic acid solution obtained in the previous step, and load them into a syringe. Use the syringe to add and fill the microneedle mold. Then use a centrifuge to adjust the speed to 5000-5500 r / min and the centrifugation time to 2 min. After centrifugation, take out the mold and scrape off the polylactic acid solution to obtain a polylactic acid drug-releasing needle tip base containing porous chitosan microspheres. Then, spread a layer of binder solution on the polylactic acid drug-releasing needle tip base containing porous chitosan microspheres, let it stand, and then add nanocellulose slurry until the mold is completely filled. Dry it at room temperature at 30°C for 6 hours or in an oven at 40°C for 3 hours, then continue to add nanocellulose slurry until the mold is completely filled, and then dry it at room temperature at 30°C for 6 hours or in an oven at 40°C for 3 hours, then take it out and separate it from the mold.
[0012] Degassing operation during microneedle preparation In the process of preparing microneedles by conventional solution method, the degassing operation is generally to remove the bubbles in the solution and between the solution and the mold by vacuuming. However, during the experimental operation of this design, it was found that the vacuuming method was not suitable for preparing the microneedles designed in this design. Since the solvent of the polylactic acid solution is dichloromethane, which evaporates quickly as an organic solvent, the vacuuming operation can easily cause the solvent to evaporate too quickly, and then form a layer of polylactic acid film on the top of the solution, causing the bubbles to be trapped in the solution and difficult to remove. Therefore, it was decided to use the centrifugal method to remove the bubbles, that is, to cover the microneedle mold with the solution, place it in a centrifuge tube, and use a centrifuge to centrifuge to achieve the purpose of degassing.
[0013] During the drying process, attention should be paid to temperature control. If the temperature is too high during the drying process, bacterial cellulose is prone to bending, resulting in warping, wrinkling, layer separation, etc. of the prepared microneedles. If the temperature is too low during the drying process, the solvent may evaporate more slowly, affecting the progress of the experiment and even making it difficult to dry completely.
[0014] Furthermore, the mass of the binder solution is 5% to 10% of the total added mass of the bacterial cellulose pulp.
[0015] Furthermore, the cellulose patch layer can also be a pre-prepared nanocellulose sheet, and the thickness of the sheet is controlled to be 0.5mm-1.5mm; after the needle tip is installed in the mold and the adhesive is poured, the sheet is covered and dried to form.
[0016] Furthermore, the cellulose patch layer can also be directly obtained using commercial bacterial cellulose thin gel mask material.
[0017] Beneficial effects of the present invention: The invention discloses a polylactic acid / nanocellulose composite microneedle patch and a preparation method thereof. The polylactic acid / nanocellulose composite microneedle patch comprises a nanocellulose patch layer substrate and a microneedle array; the microneedle array is formed on the nanocellulose patch layer substrate; the microneedles are composite microneedles, the microneedles comprise a polylactic acid drug-releasing needle tip containing porous chitosan microspheres, a nanocellulose patch layer, and a compatible bonding interlayer between the polylactic acid drug-releasing needle tip containing porous chitosan microspheres and the nanocellulose patch layer; the polylactic acid containing porous chitosan microspheres is used as the drug-releasing needle tip material and attached to the nanocellulose patch; the needle tip is connected to the patch layer by using a bonding agent of polypropylene glycol or polyethylene glycol or polyethylene glycol-b-polypropylene glycol copolymer, so as to prepare a microneedle patch with high biocompatibility, low toxicity, low cost, excellent mechanical properties and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The present invention is described in detail below in conjunction with the accompanying drawings: Figure 1 is a cross-sectional SEM photograph of the polylactic acid / nanocellulose composite microneedle patch using PPG as a binder in Example 1, wherein (a) and (b) are cross-sectional views at two different viewing angles, respectively; Figure 2 This is a SEM photo of the PLA multilayer microneedles loaded with porous chitin microspheres with PPG as an interlayer in Example 1; Figure 3 is a line graph of the compression performance test of the PLA microneedle tip in Example 1; Figure 4 1 is a top view and detail view of the microneedle mold of Example 1; Figure 5 is a front perspective view and detail view of the microneedle mold of Example 1; Figure 6 1 is a SEM photo of a cross section of a microneedle of a PLA / BC microneedle patch of control example 1, wherein (a) and (b) are top views of the needle tip, and (c) and (d) are side views of the needle tip; Figure 7 is a SEM photograph of a cross section of a microneedle of a PLA / BC microneedle patch of control example 1, wherein (a) is a cross-sectional view of the bonding surface, and (b) is an overall cross-sectional view of the microneedle patch and the needle tip; Figure 8 These are SEM images of the microneedle cross-sections of the PLA / PVB / BC microneedle patch and the PLA / PEG / BC microneedle patch of Control Example 2, wherein (a) a multilayer microneedle with PVB as an interlayer; and (b) a multilayer microneedle with PEG as an interlayer. DETAILED DESCRIPTION
[0019] The present invention is described below with specific examples, but is not intended to be limiting of the present invention.
[0020] The raw materials and equipment used are as follows: Raw materials and equipment: polylactic acid (PLA number average molecular weight 75,000, from Fengyuan Biomaterials Co., Ltd.), polypropylene glycol (number average molecular weight 2000, from Aladdin), bacterial cellulose (from Hainan Guangyu Biotechnology Co., Ltd.), chemical mechanical cotton pulp nanocellulose (average width 35nm, aspect ratio 50 from Zhongxiang Jinhanjiang); wood pulp nanocellulose (average width 35nm, length > 1μm from Kaiyi CNF); bamboo pulp nanocellulose (Ruiniuneng ring diameter 100nm, length 100μm); porous chitin microspheres made in the laboratory (patent CN 116376873 A), dichloromethane (CH2Cl2): Tianjin Yongda Chemical Reagent Co., Ltd.; electronic balance BSA124S-CW; high-speed centrifuge H1850R Xiangyi; universal testing machine UTM24059 Shenzhen Sansi Zongheng; constant temperature heating electromagnetic stirrer DF-101S Wuhan Delixiang; field emission electron microscope MIRA3; electric constant temperature blast drying oven DHG-9140 Shanghai Sanfa; pure transparent PDMS material microneedle mold of Henan Micro-Nano Pentium Biotechnology Co., Ltd., the relevant parameters of the mold are: needle shape: regular tetrahedron, needle length: 600μm, bottom side length: 300μm×300μm, needle tip spacing: 600μm, array number: 20×20, overall patch size: 15mm×15mm, groove depth: 2mm. The microneedle mold is shown in the figure Figure 4 and Figure 5 shown. Example 1
[0021] Preparation of compatible polylactic acid / bacterial cellulose composite microneedle patch: 1.1 Prepare the required liquid: (1) Preparation of polylactic acid solution: Weigh 5.00 g of polylactic acid (PLA) using an electronic balance and 45 g of dichloromethane solution, add them into a sealed glass bottle equipped with a magnetic stirrer, and stir at room temperature for 12 hours.
[0022] (2) Preparation of polypropylene glycol solution: Use an electronic balance to weigh 3.00 g of polypropylene glycol (PPG) and 45 g of ethanol, add them into a sealed glass bottle equipped with a magnetic stirrer, and stir at room temperature for 12 hours.
[0023] (3) Preparation of bacterial cellulose pulp: Take 5 g of bacterial cellulose (BC) and add it to 100 ml of water. Place it in a high-pressure homogenizer at 100 MPa to crush it to make bacterial cellulose pulp.
[0024] 1.2 Preparation of polylactic acid / bacterial cellulose composite microneedle patch by solution method: The materials required for preparing the microneedles are dissolved in a solution, the solution is added into a microneedle mold, and the solution is degassed and dried to obtain a microneedle sample.
[0025] The steps for making the microneedle sample are as follows: add 10% by mass of dry porous chitosan microsphere powder to the prepared polylactic acid solution, load them together into a syringe, inject them into the microneedle mold, and fill the needle tip of the microneedle mold. Quickly cover the lid, place it in a centrifuge tube, and centrifuge it using a centrifuge (H1850R, Xiangyi Centrifuge Instrument Co., Ltd.). At room temperature of 30°C, adjust the speed to 5500r / min, centrifuge time for 2min, and use centrifugation to better remove bubbles in the solution and between the solution and the mold. After centrifugation, remove the mold and scrape off the excess PLA solution. Next, spread a layer of polypropylene glycol solution on the PLA needle tip base, let it stand, and then add bacterial cellulose slurry until the mold is completely filled, and dry it in a 40°C oven for 3 hours. The mass of polypropylene glycol solution is 10% of the total added mass of bacterial cellulose pulp. Bacterial cellulose pulp is added to the partially dried microneedle mold of the sample until the mold is completely filled. Then it is dried in an oven at 40°C for 3 hours and the finished product is taken out to obtain a PLA, chitin microsphere, PPG, and BC composite microneedle with PLA as the needle tip and a PLA / chitin microsphere drug-carrying layer, PPG as a compatible interlayer, and bacterial cellulose as a patch layer substrate.
[0026] Cross-sectional morphology characterization of PLA / BC composite microneedle patch: Figure 1 This is a cross-sectional SEM photograph of the PLA / BC composite microneedle patch with PPG as a compatible interlayer in Example 1. The cross-sectional morphology of the PLA multilayer microneedle with PPG as an interlayer was characterized by scanning electron microscopy (SEM). Figure 1 From the four pictures, we can conclude that the gaps between the three layers of the microneedle are small, the connection is tight, and the compatibility between the layers is good, which meets the requirements of the experimental design. The needle tip layer of polylactic acid and the patch layer of bacterial cellulose are also clearly layered, and the fibrous morphology of bacterial cellulose is clearly visible. The multilayer microneedles prepared in this way meet the target requirements.
[0027] Drug loading of PLA / BC composite microneedle patch: magnified scanning electron microscopy (SEM) Figure 1 The local area of the needle tip can be obtained by SEM Figure 2 , the microsphere morphology is clearly visible, and the chitin microspheres are widely distributed in the microneedle tip; the addition of chitin porous microspheres can simulate the drug loading of microneedles, and can also be used as a drug-loading porous carrier to control the slow release of drugs, and can also increase the strength of the microneedle tip. In short, the microspheres give the microneedle high drug loading and sustained release, and are capable of loading relevant therapeutic drugs.
[0028] Mechanical strength of needle tip: Example 1 The compression performance test results of the microneedle tip of the PLA / BC composite microneedle patch with PPG as the compatible interlayer are shown in Table 1. The microneedle tip strength is measured by testing the compression performance of the PLA-based needle tip. The compression test is a test method that describes the behavior of a material under a compressive load and a uniform loading rate. Like tensile and impact properties, the compression properties of plastic materials are also basic mechanical properties, which are widely used in quality control of the production process and as a basis for engineering design. Through the compression test, a series of data on compression properties can be obtained, such as elastic modulus, yield stress, compression strength, compression strain, etc. The compression performance test of plastics is carried out according to the standard method for determining the compression properties of plastics in GB / T1041-2008.
[0029] Table 1. PLA microneedle tip compression performance test results
[0030] Figure 3 The following is a line chart of the compression performance test of PLA microneedle tips. Some experimental results of the compression performance test of PLA-based tips are shown in Table 1. According to the above chart, samples 1 to 4 are compressed to 18N, indicating that the microneedle tips made of polylactic acid have good compression resistance and excellent mechanical properties. And according to the data and Figure 3 Analysis showed that the needle tips of the microneedle array did not break or damage, showing a certain toughness and mechanical tolerance, able to maintain the original geometric shape and structural integrity.
[0031] Note: Scanning electron microscope test: Use a scanning electron microscope (MIRA, TESCAN) to characterize the cross-section of the microneedle to observe the morphology of the microneedle tip and whether there are gaps between the layers of materials, so as to compare the compatibility differences between the layers of materials and determine the most suitable interlayer material.
[0032] Compression performance test: PLA microneedles were cut into 5×5 microneedle matrices, and their compression performance was tested using a universal testing machine. During the compression test, the sample was compressed along the main axis direction of the 5×5 microneedle matrix sample at a pressure of 18N and a constant speed of 1mm / min until the sample was damaged or reached a load of 18N or the reduction in sample length reached a predetermined value of 0.51mm, and the load of the sample during this process was measured. Comparative Example 1
[0033] Preparation of PLA / BC microneedle patch (PLA and BC double-layer microneedle patch): The same polylactic acid solution and bacterial cellulose pulp as in Example 1 are used, but polypropylene glycol solution is not used. The production steps are as follows: the prepared polylactic acid solution is added to the microneedle mold using a syringe, and the amount of injected polylactic acid solution fills the needle tip part of the microneedle mold. Quickly cover the lid, place it in a centrifuge tube, and centrifuge it using a centrifuge (H1850R, Xiangyi Centrifuge Instrument Co., Ltd.). At room temperature of 30°C, adjust the speed to 5500r / min, the centrifugation time is 2min, and the bubbles in the solution and between the solution and the mold are better removed by centrifugation. After centrifugation, take out the mold, scrape off the excess PLA solution, and then add bacterial cellulose slurry until the mold is completely filled, and dry it in a 40°C oven for 3 hours. Add bacterial cellulose slurry to the partially dried microneedle mold of the sample until the mold is completely filled, and then take out the finished product after drying in a 40°C oven for 3 hours with PLA as the needle tip and bacterial cellulose as the patch layer substrate PLA / BC microneedle patch.
[0034] Morphological characterization of the cross section of the microneedle tip of the PLA / BC microneedle patch: Figure 6 This is a SEM photo of the needle tip of the microneedle in the PLA / BC microneedle patch. The morphology of the cross section of the needle tip was characterized by scanning electron microscopy (SEM). Figure 6 The four pictures in the figure are SEM images of the needle tip of the PLA microneedle, where (a) and (b) are top views of the needle tip, and (c) and (d) are side views of the needle tip. Figure 6 From the top view in (a), it can be seen that the microneedle tips are evenly distributed in a matrix with good order. Figure 6 As can be seen in (a) and (b), the prepared microneedle is in the shape of a regular quadrangular pyramid. This needle shape uses the four edges of the pyramid to easily pierce the human skin and fully deliver the drug carried by the microneedle into the human body. Figure 6 In (c) and (d), the geometric shape of the microneedle tip and the sharpness of the tip can be clearly seen.
[0035] Morphological characterization of the cross section of the PLA and BC double-layer microneedles of Control Example 1: The cross section of the PLA and BC double-layer microneedles was morphologically characterized by scanning electron microscopy (SEM). Figure 7 The two pictures in the figure are SEM images of the cross-section of the PLA and BC double-layer microneedles, where (a) is the cross-sectional view of the joint surface, and (b) is the overall cross-sectional view of the microneedle patch and the needle tip. Figure 7 It can be seen from (a) and (b) that there is a large gap between the needle tip layer and the patch layer of the double-layer microneedle, that is, the compatibility between the PLA material layer and the BC material layer of the PLA and BC double-layer microneedle prepared by the solution method is poor, which does not meet the design requirements.
[0036] In summary, polylactic acid (PLA) was selected as the microneedle tip and bacterial cellulose was selected as the microneedle patch to make a double-layer microneedle. However, the material compatibility between the prepared double-layer microneedle tip layer and the patch layer was poor and easy to separate. The characterization results of scanning electron microscopy were also poor, and there was a large gap between the two layers. Comparative Example 2
[0037] Preparation of PLA / PVB / BC microneedle patches and PLA / PEG / BC microneedle patches: The same polylactic acid solution and bacterial cellulose pulp as in Example 1 were used, but the polypropylene glycol solution was not used. PVB and PEG ethanol solutions of the same concentration were used to replace the polypropylene glycol solution. The remaining preparation steps were the same as in Example 1.
[0038] Morphological characterization of PLA / PVB / BC microneedle patches and PLA / PEG / BC microneedle patches: Figure 8 These are SEM images of the microneedle cross-sections of the PLA / PVB / BC microneedle patch and the PLA / PEG / BC microneedle patch of Control Example 2.
[0039] The cross-section morphology of PLA multilayer microneedles with PVB and PEG as compatible bonding interlayers was characterized by scanning electron microscopy (SEM). Figure 8 The cross-sectional SEM images of PLA multilayer microneedles with PVB or PEG as compatible bonding interlayers. Figure 8 The three electron microscope images in the figure show that no matter it is the multilayer microneedle with PVB as the compatible bonding interlayer or the multilayer microneedle with PEG as the compatible bonding interlayer, there are large gaps between the three layers of materials, and the three layers of materials are detached from each other. It can be concluded that the compatibility of the various layers of materials of the PLA multilayer microneedle with PVB or PEG as the compatible bonding interlayer prepared by the solution method is poor, which does not meet the requirements of the experimental design. Example 2
[0040] Polylactic acid, dichloromethane, polypropylene glycol, bacterial cellulose and microneedle mold are the same as those in Example 1.
[0041] 2.1 Prepare the required liquid: (1) Preparation of polylactic acid solution: Weigh 4.00 g of polylactic acid and 46 g of dichloromethane solution using an electronic balance, add them into a sealed glass bottle equipped with a magnetic stirrer, and stir at room temperature for 12 hours.
[0042] (2) Preparation of polypropylene glycol solution: Weigh 3.00 g of polypropylene glycol and 57 g of ethanol using an electronic balance, add the mixture into a sealed glass bottle equipped with a magnetic stirrer, and stir at room temperature for 12 hours.
[0043] (3) Bacterial cellulose sheet: Take 5 g of bacterial cellulose (BC) and add it to 100 ml of water. Place it in a high-pressure homogenizer at 100 MPa to break it up to make bacterial cellulose slurry.
[0044] 2.2 Preparation of polylactic acid / bacterial cellulose composite microneedle patch by solution method: The materials required for preparing the microneedles are dissolved in a solution, the solution is added into a microneedle mold, and the solution is degassed and dried to obtain a microneedle sample.
[0045] The steps for making microneedle samples are as follows: add the prepared polylactic acid solution into the microneedle mold using a syringe, and fill the needle tip of the microneedle mold with the amount of injected polylactic acid solution. Quickly cover the lid, place it in a centrifuge tube, and centrifuge it using a centrifuge (H1850R, Xiangyi Centrifuge Instrument Co., Ltd.). At room temperature of 30°C, adjust the speed to 5000r / min, centrifuge time for 2min, and use centrifugation to better remove bubbles in the solution and between the solution and the mold. After centrifugation, remove the mold and scrape off the excess PLA solution. Then spread a layer of polypropylene glycol solution on the PLA needle tip base, let it stand, and then add bacterial cellulose slurry until the mold is completely filled, and dry it at room temperature of 30°C for 6 hours. The mass of the polypropylene glycol solution is 5% of the total added mass of the bacterial cellulose pulp. The bacterial cellulose pulp is added to the partially dried microneedle mold of the sample until the mold is completely filled. Then it is dried at room temperature of 30°C for 6 hours to obtain the finished PLA, PPG, and BC composite microneedles with PLA as the needle tip, PPG as the compatible bonding interlayer, and bacterial cellulose sheet as the patch layer. Example 3
[0046] Polylactic acid, dichloromethane, polypropylene glycol, bacterial cellulose and microneedle mold are the same as those in Example 1.
[0047] 2.1 Prepare the required liquid: (1) Preparation of polylactic acid solution: Weigh 4.5 g of polylactic acid and 46 g of dichloromethane solution using an electronic balance, add them into a sealed glass bottle equipped with a magnetic stirrer, and stir at room temperature for 12 hours.
[0048] (2) Preparation of polypropylene glycol solution: Weigh 3.00 g of polypropylene glycol and 47 g of ethanol using an electronic balance, add the mixture into a sealed glass bottle equipped with a magnetic stirrer, and stir at room temperature for 12 hours.
[0049] (3) Bacterial cellulose sheet: Take a 1 mm thick sheet of bacterial cellulose gel block, boil it in a 10% sodium hydroxide aqueous solution for 4 h, wash it with water until it is neutral, and set aside. Take 5 g of bacterial cellulose (BC for short), add it to 100 ml of water, place it in a high-pressure homogenizer at 100 MPa to break it up to make bacterial cellulose pulp.
[0050] 2.2 Preparation of polylactic acid / bacterial cellulose composite microneedle patch by solution method: The materials required for preparing the microneedles are dissolved in a solution, the solution is added into a microneedle mold, and the solution is degassed and dried to obtain a microneedle sample.
[0051] The steps for making the microneedle sample are as follows: add 5% dry porous chitosan microsphere powder by mass to the polylactic acid solution, add the prepared polylactic acid solution to the microneedle mold using a syringe, and fill the needle tip of the microneedle mold with the injected polylactic acid solution. Quickly cover the lid, place it in a centrifuge tube, and centrifuge it using a centrifuge (H1850R, Xiangyi Centrifuge Instrument Co., Ltd.). At room temperature of 30°C, adjust the speed to 5000r / min, centrifuge time 2min, and use centrifugation to better remove bubbles in the solution and between the solution and the mold. After centrifugation, remove the mold and scrape off the excess PLA solution. Then spread a layer of polypropylene glycol solution on the PLA needle tip base, let it stand, place a pre-prepared bacterial cellulose sheet with a thickness of 1.5mm in the mold, and take it out after natural drying to obtain a PLA / BC composite microneedle patch.
Claims
1. A polylactic acid / nanocellulose composite microneedle patch, characterized in that: The polylactic acid / nanocellulose composite microneedle patch comprises a nanocellulose patch layer substrate and an array of microneedles; the array of microneedles is formed on the nanocellulose patch layer substrate; the microneedles are composite microneedles, comprising a polylactic acid drug-releasing needle tip containing porous chitin microspheres, a nanocellulose patch layer, and a compatible bonding interlayer between the polylactic acid needle tip containing porous chitin microspheres and the nanocellulose patch layer.
2. The polylactic acid / nanocellulose composite microneedle patch according to claim 1, characterized in that: The nanocellulose includes any one of bacterial cellulose, cotton pulp nanocellulose, wood pulp nanocellulose, and bamboo pulp nanocellulose.
3. The polylactic acid / nanocellulose composite microneedle patch according to claim 1, characterized in that: The porous chitosan microspheres are porous microspheres with a diameter of 20 to 200 microns and are formed by weaving and winding chitosan nanofibers.
4. The polylactic acid / bacterial cellulose composite microneedle patch according to claim 1, characterized in that: The adhesive for the compatible bonding interlayer is any one of polypropylene glycol, polyethylene glycol, and polyethylene glycol-b-polypropylene glycol copolymer, or a mixed solution of two of the two.
5. The polylactic acid / nanocellulose composite microneedle patch according to claim 1, characterized in that: The patch layer substrate has a size of 15 mm×15 mm, a microneedle length of 600 μm, a bottom side length of 300 μm×300 μm, a needle tip spacing of 600 μm, and an array quantity of 20×20.
6. A method for preparing the polylactic acid / nanocellulose composite microneedle patch according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of the slurry: prepare polylactic acid into a dichloromethane solution with a final mass concentration of 8% to 10%; prepare a binder polypropylene glycol or polyethylene glycol or polyethylene glycol-b-polypropylene glycol copolymer into an ethanol binder solution with a final mass concentration of 5% to 6.25%; take nanocellulose and add it into water for homogeneous dispersion to prepare a nanocellulose pulp with a mass volume concentration of 0.5 to 0.6 g / L; (2) Add 5%-10% of dry porous chitosan microsphere powder to the polylactic acid solution obtained in the previous step, and load them into a syringe. Use the syringe to add and fill the microneedle mold. Then use a centrifuge to adjust the speed to 5000-5500 r / min and the centrifugation time to 2 min. After centrifugation, take out the mold and scrape off the polylactic acid solution to obtain a polylactic acid drug-releasing needle tip base containing porous chitosan microspheres. Then, spread a layer of binder solution on the polylactic acid drug-releasing needle tip base containing porous chitosan microspheres, let it stand, and then add nanocellulose slurry until the mold is completely filled. Dry it at room temperature at 30°C for 6 hours or in an oven at 40°C for 3 hours, then continue to add nanocellulose slurry until the mold is completely filled, and then dry it at room temperature at 30°C for 6 hours or in an oven at 40°C for 3 hours. Take it out and separate it from the mold.
7. The method according to claim 6, characterized in that The mass of the binder solution is 5% to 10% of the total added mass of the nanocellulose pulp.